2012
DOI: 10.1523/jneurosci.2501-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Within-Digit Functional Parcellation of Brodmann Areas of the Human Primary Somatosensory Cortex Using Functional Magnetic Resonance Imaging at 7 Tesla

Abstract: The primary somatosensory cortex (S1) can be subdivided cytoarchitectonically into four distinct Brodmann areas (3a, 3b, 1, and 2), but these areas have never been successfully delineated in vivo in single human subjects. Here, we demonstrate the functional parcellation of four areas of S1 in individual human subjects based on high-resolution functional MRI measurements made at 7 T using vibrotactile stimulation. By stimulating four sites along the length of the index finger, we were able to identify and locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 43 publications
11
115
0
1
Order By: Relevance
“…Compared to the primary somatosensory hand area (S1 HAND ), the within-limb somatotopy in M1 HAND is less pronounced and lacks a strict sequential mediolateral ordering of the finger representations (Rathelot and Strick, 2006;Sanes et al, 1995). In the S1 HAND , the organization and processing of tactile inputs from the periphery show a relative strict arrangement along a mediolateral axis (Martuzzi et al, 2014;Nelson and Chen, 2008;Sanchez-Panchuelo et al, 2012). Nevertheless, consistent somatotopic gradients of representation have also been reported in M1 HAND (Beisteiner et al, 2001(Beisteiner et al, , 2004Gentner and Classen, 2006;Quandt et al, 2012) despite the widespread and intermingled neural populations in the primate M1 HAND controlling finger movements (Georgopoulos et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the primary somatosensory hand area (S1 HAND ), the within-limb somatotopy in M1 HAND is less pronounced and lacks a strict sequential mediolateral ordering of the finger representations (Rathelot and Strick, 2006;Sanes et al, 1995). In the S1 HAND , the organization and processing of tactile inputs from the periphery show a relative strict arrangement along a mediolateral axis (Martuzzi et al, 2014;Nelson and Chen, 2008;Sanchez-Panchuelo et al, 2012). Nevertheless, consistent somatotopic gradients of representation have also been reported in M1 HAND (Beisteiner et al, 2001(Beisteiner et al, , 2004Gentner and Classen, 2006;Quandt et al, 2012) despite the widespread and intermingled neural populations in the primate M1 HAND controlling finger movements (Georgopoulos et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical responses to tactile events have been difficult to measure using conventional fMRI experiments. In particular, the reliable localisation and subdivision of primary somatosensory cortex (S1) has been hard to achieve We have also demonstrated that it is possible to measure the finer-scale sub-divisions of S1, using within-digit organization (base-to-tip) stimulation of digits, providing functional parcellation of Brodmann areas of human S1 (Sanchez-Panchuelo, Besle et al 2012). We have assessed the relationship between these functional domains and underlying structure by inspecting our functionally parcellated Brodmann areas for differences in cortical thickness and alternative MR contrast measures.…”
Section: High Spatial Resolution Mapping Of Somatosensory Cortexmentioning
confidence: 99%
“…mapped to separate areas of the body (Sanchez-Panchuelo et al, 2012)). Functional connections may be investigated between any pair of sub-regions within the sensori-motor network, and it is entirely conceivable that temporal nonstationarity between individual voxels, or small clusters, may be (in part) due to spatial inhomogeneity within the network.…”
Section: ) Introductionmentioning
confidence: 99%